2002
DOI: 10.1038/sj.hdy.6800138
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and developmental stability in three-spined sticklebacks (Gasterosteus aculeatus L.)

Abstract: Fluctuating asymmetry, small non-directional departures from perfect symmetry in bilateral traits, results from the inability of individuals to buffer development against genetic and environmental perturbations. Fluctuating asymmetry is a widely used measure of developmental stability, and developmental stability has been hypothesised to be inversely related to heterozygosity. We compared male three-spined sticklebacks (Gasterosteus aculeatus L.) that had been inbred for one generation to outbred control males

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
1
16
0
2
Order By: Relevance
“…However, formal tests – accounting for the on average lower heterozygosity in pond populations – failed to find association between heterozygosity and FA across the populations. This finding is not completely surprising, as some other studies also found that heterozygosity had a weak, or no effect on FA [57-60]. However, given the fact heterozygosity and habitat type are tightly associated in our study, their independent effects on FA cannot be fully disentangled.…”
Section: Discussionsupporting
confidence: 65%
“…However, formal tests – accounting for the on average lower heterozygosity in pond populations – failed to find association between heterozygosity and FA across the populations. This finding is not completely surprising, as some other studies also found that heterozygosity had a weak, or no effect on FA [57-60]. However, given the fact heterozygosity and habitat type are tightly associated in our study, their independent effects on FA cannot be fully disentangled.…”
Section: Discussionsupporting
confidence: 65%
“…Surprisingly, studies made on replicate populations of sticklebacks (popular models of ecological genetics research) in this context have been conspicuously scarce until lately (but see: Mazzi et al, 2002;Melhis et al, 2012). For instance, the genetically depauperate pond populations of nine-spined sticklebacks (Shikano et al, 2010;Trokovic et al, 2012) would provide good models to study variation in segregation and drift loads in isolated replicate populations not subject to confounding effects of gene flow.…”
Section: Conservation Concerns and Valuesmentioning
confidence: 99%
“…Recently, however, asymmetry of morphological traits has been documented (Almeida et al, 2008;Lutterschmidt et al, 2016). Bilateral asymmetry, in individual and population levels of fish, was found to relate positively to a wide range of abiotic, biotic and genetic stresses (Allenbach et al, 1999;Franco et al, 2002;Estes et al, 2006), and could be sensitive to different levels of individual density in captive conditions (Leary et al, 1991) or increases under genetic stresses such as hybridization, inbreeding and loss of genetic variation (Mazzi et al, 2002;Dongen, 2006), particularly in reared fishes (Palma et al, 2001;Fessehaye et al, 2007). surprisingly we noticed some alteration in external morphology and level of 'left-right asymmetry', where some morphological characters (metric and meristic) of left and right sides differed asymmetrically in some specimens.…”
Section: Introductionmentioning
confidence: 99%